“REVOLUTIONS ARE IN SEASON”: INTERNATIONAL NEWS AGENCIES AND LATINAMERICAN POLITICS DURING THE COLD WAR - Gilardoni, Ximena Espeche (Revista de Historia Social y de las Mentalidades, 2021)
The information battles of the Bolivian and Cuban Revolutions overlaps the ones of the Cold War. It is fundamental to study the international news agencies activities that covered those revolutions. In this case, I will study Associated Press actions. I will analyze institutional paperwork, UNESCO studies concerning news agencies and revolutionary critics against them. It was a battle to stabilize information about what was the meaning of a Latin American revolution, as well as to transform it in a news material, including commercial issues.